Coping with the Inevitable Adjustment in the US Current Account - Jarrett, Peter (OECD Economics Department Working Papers, 2005)
In recent years the US current account deficit has grown to the point that most observers consider its level to be already unsustainable. Yet it seems set to continue to increase in the foreseeable future, with net foreign debt likely to surge. This paper describes the present deficit from three points of view: imbalances of imports over exports of goods, services and income; of inflows over outflows of capital; and of investment and spending over savings and income in the domestic economy. It then examines the possible causal factors for these disequilibria and goes on to describe the arguments for both optimistic and pessimistic views as to their unwinding over time. Last, it suggests a number of policy conclusions as to how the US authorities should factor the presence of the deficit into their decision-making, even though they rightly do not view it as a target outcome. The bottom line is that the importance of avoiding disincentives to save and of maintaining as much flexibility as possible in the economy is reinforced by the risks posed by the deficit. This Working Paper relates to the 2005 OECD Economic Survey of the United States (www.oecd.org/eco/surveys/us)